Directive illocutionary acts by Mario Teguh in ‘Super Show’ talk show: A pragmatics study - Jessica Angela Aziz; Sutiono Mahdi; Rosaria Mita Amalia (Proceedings of AICS - Social Sciences, 2017)
Mario Teguh is a well known motivator in Indonesia. He has attracted Massive public attention for several years through his talkshow programs in several Indonesian television channels like Golden Ways and Super Show Talkshow. The utterances of Mario Teguh in his motivational speeches can be analyzed through a pragmatics study. This research aims to describe and analyze the types of directive illocutionary acts and illocutionary function uttered by Mario Teguh in some videos of Super Show talk show by referring to a main theory by Searle’s, Leech theories, McManis and Yule theories. By observing the frequentative utterance of directive illocutionary acts in Mario Teguh speech, we will be able to analyze what type and function of directive illocutionary acts used by Mario Teguh. The result shows that Mario Teguh tends to use four directive illocutionary acts; they are commanding, requesting, inviting, and suggesting. The functions of directive illocutionary acts used by Mario Teguh are competitive and convivial and the contexts used in the utterances are physical, linguistic, epistemic, and social contexts.